Permians, permyaki, permichi: Who? Where? When? - Korchagin, P.A. (Perm Federal Research Centre Journal, 2020)
The derivatives of the Perm toponyms are used in many scientific texts as synonyms, regretfully, without understanding their historic, chronological and spatial reference. Meanwhile, they involve the meanings of territorial and religious affiliation, administrative regulation, moreover, their ethnic meaning in relation to the early eras is rather questionable.